A representative value for 24-hour monitored ambulatory blood pressure. - Yoo, W. S. (Korean Academy of Medical Sciences, 1986)
Several shorter-term alternatives for whole-day ambulatory monitoring of blood pressure using Pressurometer III or conventional sphygmomanometer were evaluated in 12 male patients with mild hypertension. Averages of BP reading at 8 AM once, 3 consecutive-readings either with Pressurometer or manually, serial readings for 2-hour intervals from 8-10 AM and 2-4 PM were compared with that of 24-hour ambulatory, non-invasive BP readings by Pressurometer. Both systolic and diastolic 2-hour BP averages in the morning (8 to 10 o'clock) correlated more strongly with 24-hour averages (r = 0.91 and 0.91) than the 3 consecutive (r = 0.88 and 0.66) or single (r = 0.49 and -0.35) reading alternatives did. In conclusion, the average of serial readings obtained during 2-hour monitoring period from 8 to 10 AM is a reliable predictor of 24-hour ambulatory BP and represents it more closely than the conventional single or multiple BP readings.